MANAGEMENT BANDWIDTH PADA DYNAMIC QUEUE MENGGUNAKAN METODE PER CONNECTION QUEUING (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2017)
The acceleration of the use of the internet and the need for the allocation of bandwidth needed, a method that is used for the management of internet usage and bandwidth needs. A large number of hotspots – hotspot that allows many people to connect to the device so that it requires adequate bandwidth in use. Method per connection is a queueing method that divides a large number of users in a network with a bandwidth that is provided to share the same evenly to each connected user. Method per connection queue is particularly suitable in the application where the user in a network number is dynamical.